The Evaluation Of English Textbook Entitled Active English 5 For The Fifth Grade Of Elementary School Based On Rajan's Theory - Asri, Iin Viana; , Drs. H. Djoko Srijono, M.Hum; , Dra. Dwi Haryanti, M.Hum (2013)
This research paper aims at finding out the compatibility of the English textbook entitled Active English 5 for the fifth grade of elementary school with the criteria of material design suggested by Rajan. The researcher applies descriptive research. The object of the research is compatibility the materials of English Textbook Entitled Active English 5 for the fifth grade of Elementary School with the criteria of Good Material Design by Rajan's Theory. The data of this research are the materials found in English Textbook Entitled Active English 5 written by Ida Kusuma Dewi, Djatmika, Agus Dwi Priyanto published by PT. Tiga Serangkai Pustaka Mandari in 2007. The data source is taken from Active English 5 textbook by Ida Kusuma Dewi, Djatmika, Agus Dwi Priyanto.In collecting data, the writer used documentary analysis as the instrument. The data were analyzed by (1) presenting the materials (2) comparing the materials (3) judging whether the materials of English textbook appropriate with the indicators of good materials design suggested by Sundara Rajan or not. The result shows that there are ten (10) criteria from eleven (11) criteria of Material Design Suggested by Rajan which is compatible with materials in the textbook. In some case, the writer found the possibilities of several criteria stand in the same page in the textbook The percentage is 90,90%. It means that the materials in the textbook are very good and compatible with the criteria of Material Design suggested by Rajan.The criteria of Material Design which are found in the textbook involve: 1) Motivating, the percentage is 12,50%. 2) Meaningful, the percentage is 10,93%. 3) Appropriate, the percentage is 4,79%. 4) the percentage is 8,59%. 5) Graded, the percentage is 100%. 6) Interesting, the percentage is 7,03%. 7) Interactive, the percentage is 8,59%. 8) Integrated, the percentage is 70,31%. 9) Contextual, the percentage is 10,16%. 10) Creative, the percentage is 7,03%.